Prevalence of periodontitis in rural and urban population - Kumar, Vimal Kumar; Agarwal, Vipin; Khatri, Manish; Singh, Guljot; ., Sunny (Indian Journal of Community Health, 2015)
Background: Periodontal diseases are multifactorial in origin having different forms and progression. The incidence and prevalence rates of periodontitis may be different in different areas of the World & India. Aim & Objective: To estimate the prevalence of periodontal disease. Methods & Materials: The study population consisted of multistage stratified random sample of 1280 subjects from total population of district Ghaziabad. A cross-sectional study was conducted with multi stage stratified random sampling techniques to select the sample population. The subjects were divided into different age groups and the periodontal assessment was made on the basis of, oral hygene index – simplified (OHI-S,Index), CPITN index, ESI Index. The statistical analysis was done using the CHI-Square test to determine the p value. Results: Significantly more number of females were found to be having good oral hygiene status than males. Conclusions: Significant association was observed between males and females having different scores of OHI-S, CPITN and ESI index in different age groups.